Risk factors for minor hallucinations in Parkinson's disease. (4th December 2020) - Omoto, Shusaku; Murakami, Hidetomo; Shiraishi, Tomotaka; Bono, Keiko; Umehara, Tadashi; Iguchi, Yasuyuki
Abstract : Objectives: Minor hallucinations (MHs), including sense of presence, passage hallucinations, and visual illusions, have been reported in Parkinson's disease (PD). Here, we investigated the prevalence and associated risk factors for MHs according to appearance time. Methods: Data on the clinical characteristics and the appearance time of MHs for 100 PD patients were collected using a questionnaire and analyzed. MHs were classified into two groups according to the time when MHs appeared: MHs appearing while awake during the daytime (dMHs) and MHs appearing at arousal from sleep during the night or early morning (aMHs). Results: Thirty‐eight patients (38%) experienced MHs. dMHs and aMHs were present in 21 (21%) and 28 patients (28%), respectively. Compared to patients without MHs, patients with dMHs had more severe motor symptoms, longer disease duration, higher levodopa equivalent daily dose (LEDD), and higher rates of cognitive impairment and visual hallucinations during the daytime, whereas patients with aMHs had a higher rate of rapid eye movement sleep behavior disorder (RBD), longer disease duration, higher LEDD, and higher dopamine agonist dosage. Logistic regression analysis showed that cognitive impairment was significantly associated with dMHs (odds ratio (OR) 7.292, p = .001), and that RBD (OR 8.306, p < .001) and LEDD (OR 1.002, p = .049) were significantly associated with aMHs. Conclusions: Patients with MHs have different clinical characteristics according to the time when MHs appear. These findings have important clinical and prognostic implications and suggest appropriate therapeutic options for psychotic symptoms.